The Influence of Transformational Leadership Style and Work Environment on Health Center Employee Job Satisfaction - Sumarsi, Sumarsi (Journal of Industrial Engineering & Management Research, 2019)
This study aims to determine whether transformational leadership style and work environment have a positive effect on employee job satisfaction. This research was conducted at a puskesmas in Pati district with a total of 240 employees using non-random sampling method and statistical analysis with Partial Least Square Structural Equation Modeling (PLS-SEM). The results showed that there was a positive and significant effect of transformational leadership style and work environment on job satisfaction of millennial generation employees of the Ministry of Trade. This research is expected to be input for organizations to be able to manage transformational leadership styles and a better work environment in order to provide greater job satisfaction for employees, especially the millennial generation so that employee performance can increase and organizational goals are achieved.